Pengaruh Kepemimpinan Islami dan Religiusitas terhadap Kinerja Karyawan - Desri, Suryatman; Nazaruddin, Erizal; Sabila, Salima Sindi; Alfiana, Meza Putri (Lembaga Yasin AlSys, 2023)
The purpose of this research is to examine the effect of Islamic leadership and religiosity on employee performance in organizations. Transformational theory and Islamic work ethics are the theoretical foundations of this research. Previous studies have shown that Islamic leadership and individual religiosity have a positive effect on employee performance through factors such as job satisfaction, organizational commitment, and Islamic work ethics. This study uses secondary research methods by collecting relevant and publicly available data from previous studies. The data will then be processed using descriptive analysis techniques to provide an overview of the relationship between research variables. The results of the analysis show that Islamic leadership has an effect on employee performance, but religiosity has no significant effect on employee performance. This shows that leaders who apply the concept of Islamic leadership and pay attention to the spiritual aspects of their subordinates can positively influence their performance.